(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
The concept of Quality by design (QbD) has recently gained importance in the area of analytical method development and involves understanding of the critical factors and their interaction effects by a desired set of experiments. So, the present work describes the development of Reverse Phase-High Performance Liquid Chromatography (RP-HPLC) method by QbD approach using Design of Experiments and subsequent validation for analysis of Vildagliptin in bulk drug and its pharmaceutical formulation. An efficient experimental design based on systematic scouting of all three key components of the RP‐HPLC method (Buffer pH, Organic Phase-% acetonitrile, Organic Modifier-Methanol) is presented. The significance and interaction effects of these parameters on the response variables (Retention time and tailing factor) were evaluated through statistical analysis tools like Analysis of Variance (ANOVA) and plots which revealed the final chromatographic conditions of the method. The developed method was validated and Forced degradation studies were also carried out in order to determine the stability-indicating nature of the method. The chromatographic separation was achieved on Jasco CrestPack RP C18 (250 × 4.6 mm, 5μ) column using Buffer (pH 6): Acetonitrile: Methanol (70:10:20 v/v) as mobile phase and detection was done using Photo-Diode Array (PDA) detector at 210 nm. The developed method of Vildagliptin is linear over a range of 5-15μg/ml having correlation coefficient R2 value as 0.999. The %RSD for precision and accuracy of the method was found to be less than 2%. Forced Degradation studies revealed that the method was found to be stability-indicating. The results showed that the proposed method is suitable for the precise and accurate determination of Vildagliptin in bulk and its formulation.